Estimasi Proporsi Penduduk Korban Pencurian di Provinsi Sulawesi Selatan 2020 dengan Small Area Estimation (SAE) - Reskika Rahmadani; Cucu Sumarni (Politeknik Statistika STIS, 2022)
Victims of theft are used as a negative indicator in measuring the sense of security of an area. So, the higher the crime victim is an indication that the community feels insecure. The presentation of estimates from data on victims of theft to the district/city level is very much needed as data for planning the security system in South Sulawesi Province. This is in line with the 16th target of the Sustainable Development Goals (SDGs), which is to promote the state based on law at the national and international levels and ensure equal access to justice for all. The Small Area Estimation (SAE) method can be used to overcome this limitation problem by estimating the proportion of victims of theft up to the district/city level. This estimation is carried out by borrowing the strength of several other variables from the Village Potential data (PODES) which is strongly correlated with the proportion of victims of theft by applying the Emprical Best Linear Unbiased Predictor-Fay Herriot (EBLUP-FH) method. The results showed that the SAE of the EBLUP-FH method had a smaller Relative Standard Error (RSE) than the direct estimation method.